Simulation and experimental study on processing behavior of coronary artery calcified tissue removal - Chuhang Gao; Jialiang Zhu; Fan Wu; Ziyu Cui; Mingcheng Fang; Zhaoju Zhu; Bingwei He (Scientific Reports)
Abstract Coronary artery atherosclerosis is a prevalent cardiovascular disease and a leading cause of major adverse cardiovascular events (MACE). Rotational atherectomy (RA) is an effective interventional technique for treating severe calcified stenosis. However, excessive forces, heat, and debris are prone to lead to serious surgical complications, such as slow flow/no-reflow and blood clots. To mitigate excessive force and heat generation during RA, a novel high-performance cutting tool was designed and fabricated for coronary artery calcified tissue removal. An RA simulation model was developed to simulate the procedure. The results showed that the forces, temperatures, and debris size remained within predefined safety thresholds. Using the 1.5 mm tool as an illustration, the peak cutting force was 1.062 N, and the peak temperature rise reached 1.170 °C. Debris distribution exhibited a normal pattern, with 90% of particles measuring below 14 μm. The experimental results closely matched the simulation values, showcasing errors under 10% and affirming the simulation model’s precision. This research provides theoretical support for the study of mechanisms and contributes to optimizing the effectiveness of RA.